Hambatan Ekspresi Vascular Endothelial Growth Factor oleh Ekstrak Daun Sambung Nyawa pada Endotel Membran Korioalantois (EFFECTIVITY OF SAMBUNG NYAWA LEAF EXTRACT TO INHIBIT VASCULAR ENDOTHELIAL GROWTH FACTOR EXPRESSION ON ENDOTHELIALS OF CHORIOALLANTOIC - Hamid, Iwan Sahrial; Nazar, Dady Soegianto; Ratnani, Hermin (Jurnal Veteriner; Vol 14 No 1 (2013), 2013)
Angiogenesis is the new blood vessels formation normality and important on growth and developmentof individu. Angiogenesis also have contribution to carcinogenesis or uncontrolled and malignant cancercell development, become pathologic condition like inflammatory and infection. The purpose of this researchfor knew the effectivities of Gynura procumbens extract on various dose for inhibition Vascular EndothelialGrowth Factor (VEGF) expression. This research was done to effort cancer progress inhibition. However,angiogenesis is part of carcinogenesis causes. The Chorio Allantoic Membrane (CAM) methods was usedfor this aim. Eggs at the age of nine days were divided into 6 groups. Group I were negative control ofvehicle, group II were zero treatment: 60 ng bFGF which aplicated into paper dish. The next four groupswere extract of Gynura procumbens that divided in four dose: 60, 75, 90 and 110 µg + bFGF 60 ng whichapplicated into  paper dish.  At the twelve days old, VEGF expression analysis was done whichimunohystochemical method with anti VEGF’s antibody. The result of this research showed that therewas significant different (p<0.05) on give of Gynura procumbens extract to VEGF expression. The mostsignificant VEGF inhibition by Gynura procumbens extract with dose 110 µg. The conclusion on this studywas Gynura procumbens extract effective to inhibit the VEGF expression on CAM embrio chick.
Keywords: Angiogenesis, VEGF, Gynura procumbens, CAM